Transformation of the Da'wah Strategy of the NIDA Institute of Pesantren Mudi Mesra Aceh in facing the Digitalisation Era - Syobah, Sy. Nurul; Suteja, Jaja; Masseni, Masseni; Kahinah, Dwi Iin; Rezeki, Syailendra Reza Irwansyah (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose – The purpose of this research is to review the transformation of Islamic da'wah strategies in the digitalization era, especially the da'wah strategies implemented by the NIDA Institute of Pesantren Mudi Mesra Aceh.Method – This research is field research. This research aims to analyze the phenomenon and dynamics of da'wah activities carried out by the NIDA Institute of Pesantren Mudi Mesra Aceh in the community. The type of research used is qualitative research. The data collection technique was carried out using the interview method with the manager of the NIDA Institute of Pesantren Mudi Mesra Aceh. The research data was analyzed using qualitative data analysis techniques.Results – This research highlights the challenges faced by Islamic da'wah institutions in the digital era, such as the use of technology by the younger generation, ideological polarisation, and limited financial resources, as well as the solutions applied by the NIDA Institute of Pesantren Mudi Mesra Aceh in facing these challenges.Implications –NIDA Mudi Mesra Aceh, as a forum for the da’i community of students of Islamic boarding school, adjusted their da'wah approach by utilizing social media such as Facebook, Instagram, and Twitter. They also adopt online programs such as webinars, podcasts, and online courses to reach a wider audience. In addition, NIDA Mudi Mesra Aceh is active in organizing humanitarian activities, providing assistance to communities in need, and nurturing the younger generation through leadership training programs.Originality/Value – This research is the first study to examine the transformation of the digital da'wah strategy of the NIDA Institute of Pesantren Mudi Mesra Aceh.***Tujuan - Tujuan dari penelitian ini adalah untuk meninjau transformasi strategi dakwah Islam di era digitalisasi, khususnya strategi dakwah yang diterapkan oleh Institut NIDA Pesantren Mudi Mesra Aceh.Metode - Penelitian ini adalah penelitian lapangan. Penelitian ini bertujuan untuk menganalisis fenomena dan dinamika kegiatan dakwah yang dilakukan oleh Institut NIDA Pesantren Mudi Mesra Aceh di masyarakat. Jenis penelitian yang digunakan adalah penelitian kualitatif. Teknik pengumpulan data dilakukan dengan metode wawancara dengan manajer Institut NIDA Pesantren Mudi Mesra Aceh. Data penelitian dianalisis dengan teknik analisis data kualitatif.Hasil - Penelitian ini menyoroti tantangan yang dihadapi lembaga dakwah Islam di era digital, seperti penggunaan teknologi oleh generasi muda, polarisasi ideologis, dan sumber daya keuangan yang terbatas, serta solusi yang diterapkan oleh Institut NIDA Pesantren Mudi Mesra Aceh dalam menghadapi tantangan ini.Implikasi - NIDA Mudi Mesra Aceh, sebagai tempat bagi komunitas da'i dari siswa pesantren, menyesuaikan pendekatan dakwah mereka dengan memanfaatkan media sosial seperti Facebook, Instagram, dan Twitter. Mereka juga mengadopsi program online seperti webinar, podcast, dan kursus online untuk menjangkau audiens lebih luas. Selain itu, NIDA Mudi Mesra Aceh aktif dalam mengorganisir kegiatan kemanusiaan, memberikan bantuan kepada masyarakat yang membutuhkan, dan membimbing generasi muda melalui program pelatihan kepemimpinan.Orisinalitas/Nilai - Penelitian ini merupakan studi pertama yang meneliti transformasi strategi dakwah digital dari Institut NIDA Pesantren Mudi Mesra Aceh.